Shielding Effects of Surrounding Buildings on Wind Loads on Low-Rise Building Roofs. Issue 2 (February 2014) - Quan, Y.; Gu, M.; Tamura, Y.; Matsui, M.; Cao, S.Y.; Yoshida, A.; Xu, S.; Sun, F.J.
Low-rise buildings are often built in groups, and their wind loads differ from those on isolated buildings. In this study, the wind pressures on flat roofs of low-rise buildings surrounded by similar buildings were measured with a series of wind tunnel tests. The general properties of the shielding effects of surrounding buildings were discussed. The effects of area density, relative height, and arrangement patterns of the surrounding buildings on the shielding factors of the smallest minimum negative extreme wind pressure coefficients and of the largest peak uplift force coefficients on the whole roof of the shielded building for all wind directions were analyzed. For practical purposes, both shielding factors were expressed as equations of the building area density and the relative height of the surrounding buildings based on the wind tunnel test data, which can cover most of the test results.